Epigenetic Regulatory Mechanisms Distinguish Retinoic Acid-mediated Transcriptional Responses in Stem Cells and Fibroblasts - Kashyap, Vasundhra (American Society for Biochemistry and Molecular Biology, 2010)
Retinoic acid (RA), a vitamin A metabolite, regulates transcription by binding to RA receptor (RAR) and retinoid X receptor (RXR) heterodimers. This transcriptional response is determined by receptor interactions with transcriptional regulators and chromatin modifying proteins. We compared transcriptional responses of three RA target genes (Hoxa1, Cyp26a1, RARβ(2)) in primary embryo fibroblasts (mouse embryonic fibroblasts), immortalized fibroblasts (Balb/c3T3), and F9 teratocarcinoma stem cells. Hoxa1 and Cyp26a1 transcripts are not expressed, but RARβ(2) transcripts are induced by RA in mouse embryonic fibroblasts and Balb/c3T3 cells. Retinoid receptors (RARγ, RXRα), coactivators (pCIP (NCOA3, SRC3)), and p300 and RNA polymerase II are recruited only to the RARβ(2) RA response element (RARE) in Balb/c3T3, whereas these proteins are recruited to RAREs of all three genes by RA in F9 cells. In F9, RA reduces polycomb (PcG) protein Suz12 and the associated H3K27me3 repressive epigenetic modification at the RAREs of all three genes. In contrast, in Balb/c3T3 cells cultured in the +/−RA, Suz12 is not associated with the Hoxa1, RARβ(2), and Cyp26a1 RAREs, whereas slow levels of the H3K27me3 mark are seen at these RAREs. Thus, Suz12 is not required for gene repression in the absence of RA. Even though the Hoxa1 RARE and proximal promoter show high levels of H3K9,K14 acetylation in Balb/c3T3, the Hoxa1 gene is not transcriptionally activated by RA. In Balb/c3T3, CpG islands are methylated in the Cyp26a1 promoter region but not in the Hoxa1 promoter or in these promoters in F9 cells. We have delineated the complex mechanisms that control RA-mediated transcription in fibroblasts versus stem cells.